Marginality In The Socio-Philosophical And Juridical Dimensions: The Experience Of An Interdisciplinary Approach - Borisovich Lebedev, Alexey (2019)
This article is devoted to the problem of social marginality, considered in the research key of social philosophy and the general theory of law. In recent decades, the socio-cultural reality has been significantly transformed: in the life of modern society penetrated the latest information technologies that have arisen due to the rapid development of electronics, in addition, there was the formation and spread of a new type of attitude and worldview, which was conceptualized in the philosophical, cultural, religious and other practices of globalizing space today. The epistemic field that exists between the two disciplinary practices (theory of law and social philosophy) allows us to see marginalization as an epiphenomenon of transformations of modern society.The authors begin their theoretical and applied study of marginality with a comprehensive study of its generic property, i.e. with a study of marginality as such. In this paper, we analyze the semantic and etymological meanings of marginality, consider a wide range of philosophical, sociological and historiographic issues, legal aspects that explain the generic properties of marginality, which allows, in the authors' opinion, to identify the essential and cognitive aspects of this phenomenon, to establish a causal complex of mutual influence marginality on the state of social order as well as offense, and vice versa